Environmental assessment of medium-size solar organic Rankine Cycle cogeneration plants. (August 2022) - Guillén-Lambea, S.; Pina, E.A.; Serra, L.M.; Lozano, M.A.; Lazaro, A.
Highlights: The solar plant presents better environmental results than the solar-biomass plant. ORC stands out positively with the smallest CO2 emissions of all the equipment. The storage system has the highest environmental impact, followed by the solar field. Pellet consumption represents a high share of the cumulative energy demand. The solar-only plant clearly stands as an environmentally attractive system. Abstract: The development of new clean energy production systems is one of the research priorities in the energy sector. There are numerous works that evaluate the efficiency of new energy production plants from the environmental point of view. Among them, large-scale Concentrated Solar Power plants occupy a relevant place. However, medium-size plants, between 100 KW and 10 MW, have not been evaluated as intensively, resulting in a lack of knowledge in the estimation and dissemination of inventory data and environmental assessments, especially those including Organic Rankine Cycle (ORC). This work evaluates the environmental impacts caused by two solar ORC cogeneration plants that supply electrical and cooling energy for a shopping centre located in Zaragoza (Spain), using the Life Cycle Assessment methodology. One system is hybridized with a biomass boiler and the ORC operates at full load, the second one is not hybridized and the ORC can operate at partial load depending the availability of the solar energy. The selected life cycle impact assessment methods are Global Warming Potential, ReCiPe 2016, and Cumulative Energy Demand. The results allow for evaluating and comparing the environmental loads of the two medium size cogeneration systems in order to help different stakeholders to make well-informed decisions with regard to the environment. The system without hybridization presents better environmental performance in all the applied methods, 76.7 % of CO2 emissions, 67.5% of environmental impacts according to ReciPe and 5.7% of cumulative energy demand with respect to the system with hybridization. The findings show the importance of the impacts caused during the manufacturing phase of the equipment, which are more relevant than those produced during the operation phase of the plants for all environmental indicators analysed.